THREAD, SCRAPS AND FABRIC IN THE TRADITIONAL RITUAL CULTURE OF DAGISTANIS - Musaeva, Majsarat Kamilovna (History, Archeology and Ethnography of the Caucasus, 2023)
The article focuses on identifying the role of specific elements within the “objectified” culture in the mythopoetic worldview and ritualistic practices of the Dagestani peoples. It aims to explore commonplace items like thread, scraps, and fabric, which, while being familiar in our tangible world, possess not only utilitarian functions but also distinct semiotic qualities. These items have the capacity to forge particular social connections, attributable to their utilization in the ritual culture prevalent among the majority of the Dagestani peoples. Given the contemporary impact of globalization, which often results in the erosion of historical knowledge and ideas, there is a compelling justification for documenting the material and spiritual landscape of our ancestors. This study draws on an examination of specialized literature and field data amassed by the author over numerous years of ethnographic expeditions in Dagestan. The approach involves comprehending the internal structure of developmental patterns within general and specialized scientific knowledge systems, with a particular emphasis on the role of everyday items in socially significant events. The author concludes that the central concept defining the semantic essence of thread, and its derivatives such as fabric, scraps, embroidery designs, carpets, and rugs, revolves around the interconnectedness of ideas with the destiny of life and the social bonds established through the use of thread. This connection signifies continuity and ritual connotations. Notably, thread serves as a medium through which temporal and spatial gaps are bridged, linking life with death, individuals with society, and establishing or disrupting social and mythological “dialogues.” The core of this semantic significance lies in the process of producing woven objects through weaving, where countless threads are interwoven to form a unified whole. This method, in turn, holds the potential to connect the cosmic principle with human life, as well as the world of people with the otherworldly realms, beliefs deeply ingrained in the past.
Keywords: Dagestan; material culture; thread; cloth; scraps; wedding and funerary rituals; gift exchange; semiotic and semantic load